G229 Transport medium fluid cultures in paediatric renal transplantation: are we ready to make a consensus on prophylaxis?. (May 2019) - Furnell, D; Boyle, S; Kessaris, N; Marks, SD; Stojanovic, J
Abstract : Background: The medium used in transporting donor kidneys is susceptible to bacterial growth. Practice in sending transport medium fluid(TMF) cultures differs between paediatric renal transplant centres. There is no consensus on which prophylactic antibiotic, if any, should be used and lack of published data on TMF cultures for paediatric renal transplant recipients. Methods: We analysed electronic records of 125 renal transplant recipients transplanted at a large paediatric renal transplant centre from 2013–2017. 36 had deceased donor kidney transplants (DDTx) and 89 had living donor kidney transplants (LDTx). 50 patients were excluded as no culture was sent, leaving 27 DDTx and 48 LDTx patients for analysis. We looked into TMF growth and sensitivity to the prophylactic antibiotics used. Results: 30% of the DDTx recipients had a positive TMF culture. 75% grew a single bacteria and 25% grew multiple organisms(Table 1 ).Coliforms were the most common bacteria grown(30%).Only 50% of the bacteria were sensitive to the prophylactic antibiotics used at the time (protocol revised from ciprofloxacin to co-amoxiclav in 2017). 60% of growths were sensitive to amikacin, whereas only 30% were sensitive to co-amoxiclav and 27% to ciprofloxacin. 19% of LDTx recipients had a positive TMF culture. 78% grew a single organism and 22% had multiple growths. Coagulase negative staphylococcus was most commonly grown(55%). 36% of the bacteria were sensitive to the prophylactic antibiotics. 64% of cultures were sensitive to amikacin. Only 9% were sensitive to co-amoxiclav and 27% to ciprofloxacin. Conclusions: Bacterial growth of TMF cultures differs between DDTx and LDTx. Only 30% of bacteria were sensitive to the prophylactic antibiotics. Amikacin was the antibiotic that most organisms were sensitive to in both groups although there are concerns using aminoglycosides in this patient cohort.